2013
DOI: 10.1016/j.athoracsur.2013.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Risk of Pacemaker Implantation After the Cox-Maze IV Procedure

Abstract: Background The incidence of and causes for permanent pacemaker implantation (PPM) after surgical arrhythmia procedures remain poorly understood because of the varied lesion patterns and energy sources reported in small series. This study characterized the incidence, indications, and risk factors for PPM after the Cox-maze IV (CMIV) procedure when performed as either a lone or a concomitant procedure. Methods A retrospective analysis of 340 patients undergoing a CMIV as either a lone (n = 112) or a concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 23 publications
2
21
1
1
Order By: Relevance
“…)—the patient had immediate sinus arrest during ablation requiring pacing . Interestingly, although there is proximity of ablation lesions to the atrial arterial blood supply, the rate of SND requiring pacemaker implantation in our study was far lower than that reported following the surgical maze . This may result from nontransmural lesion formation with catheter ablation, in contrast to surgical maze …”
Section: Mechanisms Of Sndcontrasting
confidence: 51%
“…)—the patient had immediate sinus arrest during ablation requiring pacing . Interestingly, although there is proximity of ablation lesions to the atrial arterial blood supply, the rate of SND requiring pacemaker implantation in our study was far lower than that reported following the surgical maze . This may result from nontransmural lesion formation with catheter ablation, in contrast to surgical maze …”
Section: Mechanisms Of Sndcontrasting
confidence: 51%
“…The most common complication was pacemaker implantation, which occurred in 17 patients (17%). This is in line with a very recent retrospective analysis of the predictors and risk of pacemaker implantation after the Cox‐Maze procedure, which found concomitant procedures to be associated with a non‐significantly higher risk than lone interventions (11% vs. 5%, p = 0.14 and 15% vs. 6%, p = 0.06, at 30 days and one year, respectively) . Another group reported a rate of pacemaker implantation at 30 days of 6.9%, in which a biatrial lesion set was the single predictor of pacemaker implantation.…”
Section: Discussionsupporting
confidence: 79%
“…This was much higher than we saw in patients undergoing a stand-alone CMPIV. (23) During the same time period our incidence of pacemaker implantation in patients undergoing isolated AVR was 6.7%. This high incidence may be explained by the older patient population and the complexity of the surgery performed in these patients.…”
Section: Commentmentioning
confidence: 73%
“…Half of the patients requiring postoperative pacemaker implantation in this group were indicated for 3 rd -degree heart block, which is rarely seen following the stand-alone CMPIV. (23) Though there is some evidence to suggest patients with sinus node dysfunction improve after the CMP lesion sets,(24, 25) further studies will be needed to assess this complication.…”
Section: Commentmentioning
confidence: 99%